Current and evolving biomarkers for precision oncology in the management of metastatic colorectal cancer - Henry, Jason Timothy; Johnson, Benny (Chinese Clinical Oncology; Vol 8, No 5 (October 09, 2019): Chinese Clinical Oncology (Molecular Markers in Colorectal Cancer), 2019)
Colorectal cancer remains one of the most common cancers worldwide and is almost uniformly fatal for those with metastatic disease. Despite this, there is an increasing number of treatments and overall survival has been increasing. Utilizing increasing knowledge of tumor biology, there have been 13 new FDA drug approvals and 5 additional drugs that appear on the National Comprehensive Cancer Network (NCCN) guidelines that await FDA approval since 2002. Still, there is great need for many patients for additional treatment options. In the following text, we review our current clinical and molecular knowledge as it pertains to treatment of patients with metastatic colorectal cancer and future directions regarding therapeutic vulnerabilities.